Detection of anti-Neospora caninum antibodies in Iranian native cattle - Gharekhani, Jamal; Heidari, Heidar (Journal of Advanced Veterinary and Animal Research, 2014)
Neospora caninum is an Apicomplexan parasite which may cause abortion in cattle. This study investigated occurrences of antibodies against N. caninum in Iranian native cattle. From September 2010 to September 2011, blood samples (n=768) of native cows were collected randomly from different rural regions of Hamedan (n=400) and Kurdistan provinces (n=368) located to the western part of Iran. All the samples were evaluated for IgG antibodies against N. caninum using Enzyme Linked Immunosorbent Assay. The IgG antibodies to N. caninum were found in 14.2% (n=109/768) of serum samples (95% CI: 11.74 - 16.66). There was a significant difference between seropositivity and abortion history (p<0.0001, OR=2.9), unlike to age groups (p=0.105). This is the first report of N. caninum infection in Iranian native cattle. In conclusion, N. caninum is an important factor in abortion in Iranian native cattle. Further comprehensive studies and designing control strategies for improving management in cattle farms are highly recommended. http://dx.doi.org/10.5455/javar.2014.a40